Pengaruh Harga Dan Lokasi Terhadap Keputusan Pembelian Produk Pada Naluri Kopi Bogor - Rama Kurnia Benny; Abdul Khoir (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This study aims to analyze the effect of price and location on product purchasing decisions at Naluri Kopi Bogor using a quantitative approach. Data was collected through questionnaires and literature studies with a sample of 100 respondents. Data analysis includes classical assumption tests, simple and multiple linear regression, correlation coefficient, coefficient of determination, and t test and F test, which are processed using SPSS version 26. The results showed that price significantly influenced purchasing decisions, with a regression equation Y = 7.654 + 0.639 X1 and a strong correlation of 0.780. Location also has a significant effect on purchasing decisions, with the equation Y = 6.458 + 0.910 X2 and a strong correlation of 0.818. Simultaneously, price and location have a significant effect on purchasing decisions with the equation Y = 4.128 + 0.243 X1 + 0.507 X2 and a coefficient of determination of 69.3%, while the remaining 30.7% is influenced by other variables outside this study. The results of hypothesis testing show that both partially and simultaneously, the price and location variables have a significant influence on purchasing decisions.